Changes on transmittance mode of different composite resins - Queiroz, Renato Souza [UNESP]; Lima, João Paulo Martins de [UNESP]; Malta, Daniel Alexandre Menezes Pedrosa [UNESP]; Rastelli, Alessandra Nara de Souza [UNESP]; Cuin, Alexandre [UNESP]; Porto Neto, Sizenando de Toledo [UNESP] (FapUNIFESP (SciELO), 2009)
The purpose of this study was to evaluate the transmittance of seven different composite resins. Ten specimens were prepared (10 mm diameter, 2 mm thickness) for each experimental group, as follows: G1- Charisma® A 2 (Heraeus-Kulzer); G2- Filtek™ Supreme A 2E (3M/ESPE); G3- Filtek™ Supreme A2B (3M/ESPE); G4-Filtek™ Supreme YT (3M/ESPE); G5- Esthet-X® A2 (Dentsply); G6- Esthet-X® YE (Dentsply); G7- Durafill® A 2 (Heraeus-Kulzer) and G8- Filtek™ Z-100 A2 (3M/ESPE). The transmittance mode was measured using a UV-visible spectrophotometer (Cary Instruments) at 400-760 nm. The specimens were evaluated at three different times: zero hour (initial), 24 hours and 10 days after immersion in artificial saliva. The differences in transmittance were determined by two-way analysis of variance (ANOVA) and Tukey's test. The various composite resins showed significant differences in the wavelength dependence of transmittance. The mean values of transmittance increased significantly, with wavelengths increasing from 400 to 760 nm. The performance of the experimental groups was similar in terms of immersion time, considering that at time zero and after 10 days, all the groups showed similar results, which were statistically higher than the values obtained after 24 hours of immersion. The Filtek™ Supreme YT composite resin presented the highest mean transmittance values along the wavelengths at the three measured times. Esthet-X® YE and Durafill® yielded similar mean transmittance values, which were higher than those of the other groups. This study shows that the transmittance values of composite resins are directly related with the type, size and amount of inorganic filler particles.
Keywords: Composite resin; Dental esthetic materials; Spectrophotometer; Transmittance; Artificial saliva; Composite resins; Experimental groups; Immersion time; Inorganic fillers; Mean values; UV-visible spectrophotometer; Wavelength dependence; Human computer interaction; Meteorological instruments; Regression analysis; Resins; Spectrophotometers; Spectrophotometry; Analysis of variance (ANOVA)